Internalisasi Nilai Tauhid Dalam Pembentukan Pola Asuh Islami: Perspektif Hukum Keluarga Islam - Hidayatullah Ismail; Dasman Yahya Ma’aly; Helmi Basri; Mohd Nooralif bin Mahari; Mochammad Novendri S (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
The weakening of spiritual awareness within modern Muslim families, as reflected in the limited attention given to early faith-based education, indicates a challenge in the internalization of tawhid values in child-rearing practices. This study aims to analyze the internalization of tawhid values in the formation of Islamic parenting patterns from the perspective of Islamic family law. The research employs a qualitative approach using a library research method, with data derived from classical and contemporary literature, the Qur’an, hadith, and family law regulations in Indonesia, including Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). The findings reveal that the internalization of tawhid values is not only a theological obligation but also possesses normative legitimacy within Islamic family law. Tawhid-based Islamic parenting is developed through parental role modeling, habituation to acts of worship, and consistent spiritual interactions within family life. Furthermore, challenges such as low levels of religious literacy and environmental influences can be addressed through strengthening the role of the family, community support, and the utilization of technology-based da‘wah media. This study highlights the importance of integrating normative (Sharīʿah-based) and social dimensions in the development of Islamic parenting practices and offers both theoretical and practical contributions to strengthening family education grounded in tawhid values